STRES PENGASUHAN DALAM PERSPEKTIF PSIKOLOGI ISLAMI: KONSEP DAN INTERVENSI - Dwi Estiningsih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study addresses the increasing parenting stress experienced by parents since the Covid-19 pandemic and highlights the lack of research grounded in Islamic Psychology. The study focuses on developing a conceptual framework of parenting stress and formulating mental-health interventions derived from the Qur’an and Hadith. Using textual study and a hermeneutic approach, contemporary parenting literature was examined alongside interpretive analysis of relevant Qur’anic verses and prophetic traditions to understand their meanings, relevance, and practical application to modern parenting contexts. The findings identify six major sources of parenting stress: responsibility demands, role conflict, economic pressure, children’s developmental and behavioral challenges, spiritual and religious concerns, and limited social support. These domains can be operationalized into measurable behavioral indicators. Proposed interventions include patience (sabr), prayer (shalat), perseverance (istiqamah), consultation and deliberation (musyawarah), and social caring, all grounded in faith through mindfulness of God, devotion, and obedience to divine guidance. The study concludes that integrating Qur’anic and Prophetic teachings within Islamic Psychology offers both conceptual clarity and practical strategies to reduce parenting stress and strengthen parental mental health. Further research is recommended to refine and empirically evaluate these interventions within parenting programs.